Humor in der Medizin – Von der Kunst, über Schatten zu springen - Wild, Barbara (DMW - Deutsche Medizinische Wochenschrift, 2017)
Humor and laughter are integral parts of human life and communication – and so of course they occur in medical contacts.Humor is defined as a personality based cognitive emotional style of processing situations, characterized by the ability to find positive aspects even in negative situations, and the ability to communicate this point of view to others and to cheer them up. Humor can support healing processes and coping with illness. Humor and jokes reduce anxiety and stress (for patients and doctors). Humorous people have a more realistic, flexible and less fearful behaviour. Humor helps to overcome negative experience. Humor can help the patient to gain new views towards the disease and a healthy distance towards occurring symptoms. Humor improves the relationship between patient and doctor. But beware: jokes can also be used to express fears, aggression or shame. Therefore it is worthwhile to listen carefully to what patients want to express. Humor reduces the risk of burnout. In contact with patients, it is important to give their humor room, to use it and respond to it, more than making jokes. Humor can be trained. Humor training and creation of a humorous atmosphere in health care facilities should also be supported by health insurance funds, institutions' sponsors and public authorities.
Keywords: Emotionale Verarbeitung; Resilienz; positive Psychologie; Bewältigungsstrategie